Teaching Students To Program In A Virtual Collaborative Environment - Dilfuza Ergashovna Saidova (Euro Asian Journal Publishing, 2024)
The article describes the model of organizing group interaction of students in developing joint projects within the framework of extracurricular programming activities using a multimedia programming environment. The author proposes a technology for organizing group interaction and provides an example of step-by-step group development.
Keywords: group learning; programming; project activities